O corpo narrado: experiência formativa no estágio supervisionado do curso de Licenciatura em Ciências Biológicas da UFPI - Gonçalves, Nilda Masciel Neiva (2019)
The study was performed in Science and Mathematics Education Research field, has as its theme the possibilities and potentialities of the narratives of the interns' bodies, in a Supervised Internship class of the Biological Sciences Degree, from the Federal University of Piauí (UFPI / CSHNB), located in Picos-PI city. This study aims to: a) analyze the curricular internship in the context of the Biological Sciences course as a space / place for (mis) construction of knowledge about the body; b) identify in narratives about body production, of a interns group, ruptures and continuities of body conceptions in teaching and initial teacher training in Biological Sciences; c) discuss the potential of formative support that can provide students' narratives in construction of articulation biological knowledge and culture in the context of Supervised Curricular Internship in a Degree Course in Biological Sciences. The conditions taken in this paper are aligned with the defenses that biological knowledge in and outside the school space should be thought of and presented in articulation with culture, in order to strengthen reflections that allow us to unveil the types of subjects and society we are producing. Thereby, this work fits into research world that disregards the valuation only of objectivity, theorizing, rationality and is based on theorists who value objectivity without detriment to subjectivity, as Le Breton (2007), Josso (2002) , Larrosa (1994), Souza (2006), Silva (2009), Foucault (1999), among others. I accept, at the time, a research with narrative whose method and methodology are based on the post (critical) fields, where experience, narratives (imagery and writing), were sources for body discussions. Experience, understood here as what we study, the narrative, a way of thinking and writing about it. Through interpretative analysis of body research, I find that narratives of the intern's body make it possible to unveil a biological and cultural body produced trajectory of life. In theory the analysis indicates that the body narratives, in the context of the Supervised Internship, constitute formative experiences that potentially contribute to disruption with conservative paradigms. Therefore, they allow the bodies understanding as hybrid production, at the interface between biological, historical and cultural dimensions, therefore from a critical perspective. That the (mis) construction of body conceptions is possible with identification of biological, social and cultural markers in narratives, whether imagetic or written, and that interformation in the context of supervised curricular internship enables perception of ruptures and continuities within biological teaching. In this sense, future teachers practice based on problematization of what build the bodies meaning, will enable the presentation of the biological / cultural body to students of Basic Education, with the intention of reducing the differences, whether biological, social, economic or cultural.